Study on Unexpected Capability of Melanin to Split the Water Molecule and the Alzheimer’s Disease - Arias-Esparza, Maria del Carmen; Arias, Ruth Isabel Solís; Arias, Paola Eugenia Solís; Arias, Martha Patricia Solís; Solís-Herrera, Arturo (Highlights on Medicine and Medical Research Vol. 9, 2021)
We began a study of the three major causes of blindness in 1990 because their incidence and prevalence had not changed in the previous forty years. Twelve years later, we discovered that water, not ATP, is the primary source of energy for the human retina. This is also valid for the human body as a whole. The main source of energy is water. The amazing capability of eukaryotic cells to break or dissociate the water molecule was unsuspected to us because it takes 2000°C degrees to dissociate water in a laboratory environment, and until today, it was believed that only plants could accomplish this. The water we drink on a regular basis isn't just for washing away dirt and toxins; it's also not just a cleaner or a basic solvent. Hydrogen may provide energy to cells as our bodies dissociate the water molecule (Hydrogen is the energy carrier that Nature uses the most). Our primary source of energy is water. If our body could not acquire energy from water, we would need to eat between 50 - 170 kg (110 - 374 lbs.) daily. In any system, when a generalized failure occurs, we must suspect energy first. Parkinson and Alzheimer’s Disease are examples of a generalized failure. That explains why it is not uncommon that patients improve dramatically with pharmacological stimulation of the human photosynthesis process. Remember that the brain requires energy not only to expand and perform functions, but also to maintain its shape and form. Hydrogen is the greatest source of energy for human cells. Chronically low levels of water dissociation in AD suggest a persistent energy deficit, which can manifest itself in a number of ways as the disease progresses.